2011
DOI: 10.2176/nmc.51.484
|View full text |Cite
|
Sign up to set email alerts
|

Radiculopathy Caused by Osteoporotic Vertebral Fractures in the Lumbar Spine

Abstract: The clinical features of radiculopathy caused by osteoporotic vertebral fractures (OVFs) in the lumbar spine were investigated in 66 patients treated for pain caused by OVFs from January 2006 to December 2009. Ten of the patients complained of persistent radiculopathy. The cause of radiculopathy was initially diagnosed as lumbar canal stenosis (LCS) in seven patients, lumbar foraminal stenosis (LFS) in two, and both in one. One patient with LFS had reduced pain with conservative treatment, and the other nine n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…3A). In the flat-type (Type 2) and concave or H-shaped type (Type 3) low lumbar OVC, neurological symptoms result from retropulsed bony fragments causing foraminal stenosis and/or canal stenosis 8,19 ( Fig. 3B and C).…”
Section: Discussionmentioning
confidence: 99%
“…3A). In the flat-type (Type 2) and concave or H-shaped type (Type 3) low lumbar OVC, neurological symptoms result from retropulsed bony fragments causing foraminal stenosis and/or canal stenosis 8,19 ( Fig. 3B and C).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have reported the surgical techniques and outcomes of OVF with neurological deficits [6][7][8][9][10][11][12][13][14][15] . Most of these studies are case series at a single or small group of institutions, and studies with large sample sizes are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…[303132] This is due to the Spine Jack ® efficient mechanical characteristic, but above all it is due to the possibility of leaving the devices into the vertebral body. This avoids vertebral body recollapsing before cement injection[56] [Figure 8].…”
Section: Resultsmentioning
confidence: 99%